Transcystic Choledochoscopy Utilizing a Disposable Choledochoscope: How We Do It. Issue 5 (9th October 2022) - Campbell, John; Pryor, Aurora; Docimo, Salvatore
Abstract : Background: Biliary disease is common occurrence and can make up a large portion of the practice of a general surgeon. Choledocholithasis is a common entity amongst those with biliary disease. Although modern trends favor endoscopic retrograde cholangiopancreatography (ERCP) and other imaging modalities for the diagnosis and management of choledocholithiasis, laparoscopic common bile duct exploration (LCBDE) is likely underutilized. Methods: A literature summary utilizing a PUBMED search was performed to provide an up-to-date account regarding the latest data on LCBDE. A video identifying and explaining the critical components of a LBCDE procedure is provided. Results: LCBDE is an underutilized procedure which offers equivalent clinical outcomes compared with ERCP along with a shorter length of stay and reduced costs. LCBDE is also noted to be an effective option for common bile duct stones in the setting of altered anatomy, such as a Roux-en-Y gastric bypass. Conclusion: Although modern trends favor ERCP and other imaging modalities for the diagnosis and management of choledocholithiasis, LCBDE is likely underutilized by surgeons. LCBDE can provide many benefits to patients including avoidance of additional procedures, shorter length of stay, higher success rates, and less costs. Out video should act is a guide for those surgeons interested in implementation LCBDE in their practice.